Tinjauan Spiritualitas Ignatian dalam Tulisan Refleksi Siswa Smk Katolik St. Mikael Surakarta (Pusat Riset dan Inovasi Nasional, 2026)
The study highlights the importance of spirituality as a foundational framework for shaping adolescents’ life orientation in the complex digital era, marked by pervasive distractions and fragmented meaning. Ignatian spirituality, emphasizing reflection and lived experience as loci of encounter with God, provides a contextual approach to help adolescents construct deeper existential meaning. The study aims to examine how reflective practices within this framework support students of SMK Katolik St. Mikael Surakarta in internalizing spiritual values and navigating digital challenges. Using a qualitative descriptive case study design, data were collected from 195 reflective writings of twelfth-grade students and reduced to 90 representative samples. The film Hacksaw Ridge was employed as a reflective stimulus to enhance affective and existential engagement. Data analysis was conducted using the four pillars of Jesuit education: Competence, Conscience, Compassion, and Commitment. The findings reveal that all reflections contain at least one element of the 4C framework integrated with Ignatian spirituality. Reflection serves not only as a medium of self-expression but also as a transformative process fostering moral awareness, social sensitivity, and commitment to action. It effectively enables students to process both personal and digital experiences into meaningful learning. The study affirms the strong relevance of integrating spirituality, reflection, and Ignatian pedagogy in contemporary education, contributing to the formation of reflective, value-oriented individuals committed to the common good.